PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK DI SMA IT IKHLAS CENDEKIA LAHAT KABUPATEN LAHAT TAHUN PELAJARAN 2022/2023 - Tubagus Muhammad As,; Abdul Adib,; Rina Setyaningsih, (UNISAN JURNAL, 2024)
This research is motivated by the role of Islamic religious education teachers in fostering student morals at IT Ikhlas Scholar High School, as many teachers do not carry out their role as teachers, especially in fostering good morals towards their students, because there are still many students who violate school regulations and even fight. towards teachers, likes playing truant and saying dirty things and so on. It's all because of the lack of attention and guidance from teachers towards students. So there are still many students who have not practiced good morals at Ikhlas Scholar IT High School. So from that moment on, moral development for student independence needs to be further improved in order to create students who have good morals and are able to become independent students. Moral development to increase students' independence so that they can achieve it, it is necessary to know and understand the factors that influence moral development to increase independence so that the expected learning goals can be achieved. This research aims to determine the role of Islamic religious education teachers in developing student morals at IT Ikhlas Scholar High School, to determine the methods of Islamic religious education teachers in developing student morals at IT Ikhlas Scholar High School, and to determine the inhibiting factors/obstacles in developing student morals. This type of research is descriptive qualitative, data collection methods use observation, interviews and documentation methods. The qualitative analysis method in collecting data is through data classification, data reduction, data description, and drawing data conclusions. The data sources for this research are primary data sources and secondary data sources. From the results of the research, the author can conclude that at SMA IT Ikhlas Scholar that the role of Islamic religious education teachers in developing students' morals is good, but there is still a lack of role models, as for the role of Islamic religious education teachers at SMA IT Ikhlas Scholar, namely as teachers, as educators, and as a coach. Then the methods of Islamic religious education teachers are the habituation method, the advice method, the assignment method, and the punishment method. The inhibiting factors/obstacles for Islamic religious education teachers in developing students' morals are the environment where students live, the influence of friends, and online games.